(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
Sustainable mobility has a goal to assure mobility, mostly in urban areas, and rationally use space and environment at the same time, not neglecting its impact and positive effects on human health and quality of life. In this paper application of this concept is presented on the example of the City of Otočac. The chosen area was the city center for which all necessary traffic and spatial analyses were done and some possible solutions for enhancing traffic conditions with minimal investments were proposed and evaluated.